Postoperative negative pressure pulmonary edema following repetitive laryngospasm even after reversal of neuromuscular blockade by sugammadex: a case report - Lee, Ji Hyeon (Korean J Anesthesiol, 2017)
Laryngospasm, an occlusion of the glottis, can occur at any time during anesthesia, and is associated with serious perioperative complications such as hypoxia, hypercabia, aspiration, bronchospasm, arrhythmia, prolonged recovery, cardiac collapse, and eventually catastrophic death. Importantly, postoperative negative pressure pulmonary edema (NPPE) is a rare, but well described life-threatening complication related to acute and chronic upper airway obstruction. Sugammadex well known for affirmatively reducing the postoperative pulmonary complications associated with residual neuromuscular blockade may have an indirect role in triggering the negative intrathoracic pressure by raising a rapid and efficacious respiratory muscle strength in acute upper airway obstruction. Herein, we report a case of postoperative NPPE following repetitive laryngospasm even after reversal of rocuronium-induced neuromuscular blockade using sugammadex.